Disordered Mother or Disordered Diagnosis? Munchausen By Proxy Syndrome - Larcher, Victor (Journal of medical ethics, 2000)
Munchausen By Proxy Syndrome (MBPS) or Munchausen Syndrome By Proxy as Meadow termed it is one of the current controversial areas of child abuse. Its diagnosis or its very existence generates as much debate as that produced by the diagnosis of sexual abuse in the 1980s.This book, whose authors are philosophers at the State University of New York, at Stony Brook, sets out to question the assumption on which the syndrome is based. They argue that the syndrome is essentially false and the evidence sustaining it insubstantial and logically flawed. This book is aimed at physicians - adult as well as paediatricians since it also considers Munchausen's Syndrome - and social and cultural theorists. The first part of the book is concerned with arguing that the construction of some disorders for example, witchcraft, hysteria and MBPS have …